Thriving on challenges: how immigrant academics regulate emotional experiences during acculturation. Issue 1 (2nd January 2020) - Antoniadou, Marilena; Quinlan, Kathleen M.
ABSTRACT: Transnational academic mobility is of growing importance in higher education. Yet, the acculturation for individual academics is challenging. Taking a phenomenological approach, we interviewed twenty foreign-born academics, who had been living and working in the UK for at least one year, and analysed their emotional experiences of acculturation by chronological stages. Then, using Gross's (Gross, J. J. 1998. "Antecedent-and Response-Focused Emotion Regulation: Divergent Consequences for Experience, Expression, and Physiology." Journal of Personality and Social Psychology 74 (1): 224–237; Gross, J. J. 2014. "Emotion Regulation: Conceptual and Empirical Foundations." In Handbook of Emotion Regulation, 2nd ed., edited by J. J. Gross, 3–20. New York: Guilford) model of emotion regulation, we analysed how participants used emotion regulation processes throughout their adaptation to their new environments. The study makes an original contribution firstly by applying a model of emotion regulation not previously used in researching academic life. Secondly, this study shows that, unlike stage theories, acculturation is not experienced primarily in linear stages, but as an ongoing process during which immigrant academics actively work on changing the things that challenge them. Thirdly, the findings emphasise the contributions rather than deficits of immigrant academics. Implications for supporting immigrant academics' acculturation are discussed.